The Interrelationship between Human Resource Roles and Human Resource Management Effectiveness: Empirical Evidence from a Developing Country - Shakil, Rashed Mahmud; Karim, Md. Arfanul; Uddin, Mohammad Jidhan; Chowdhury, Titon (Future Science / FSH-PH Publications, 2023)
The issue of effective human resource (HR) roles performance and the effectiveness of HR operations at Bangladeshi private banking sector has grown in importance over the past few decades. The scholarly literature, however, largely lacks the empirical research examining the impact of four HR roles on HRM effectiveness. The prime objective of the current research includes testing the causal relationships between four HR roles (employee champion, strategic partner, change agent, and administrative expert) and HRM effectiveness. Data was gathered from the first-line managers employed in the private commercial banks in Bangladesh (n = 210). The hypothesized model was examined utilizing partial least squares structural equation modelling, or PLS-SEM. The findings showed that the roles of employee champion, strategic partner, change agent, and administrative expert had a positive and significant impact on HRM effectiveness. The implications regarding the findings are explained and recommendations for further research are also proposed.